The study of analgesic effect of 5-(furan-2-yl, 2-methylfuran-3-yl)-4-amino-1,2,4-triazole-3-thion derivatives - D. M. Danilchenko (Zaporozhye State Medical University, 2018)
Abstract Introduction. The nucleus of 1,2,4-triazole is the subject of close attention from a wide range of scientists because of numerous unique properties. Analyzing literary sources, it should be noted that there is a large amount of information devoted to the study of analgesic activity of 1,2,4-triazole derivatives. Consequently, the search for new promising molecules among derivatives of 1,2,4-triazole, which may later be used as objects for the creation of potential analgesic agents, remains relevant, has theoretical and practical significance. The purpose of our work was to investigate the analgesic activity of 14 new derivatives of 5-(furan-2-yl, 2-methylfuran-3-yl)-4-amino-1,2,4-triazole-3-thiols, in some cases, to trace the relationship between the activity of compounds and their structure. Materials and methods. Studying of new derivatives of 5-(furan-2-yl, 2-methylfuran-3-yl)-4-amino-1,2,4-triazole-3-thion on the central component of the nociceptive system was carried out on the model of "acetic acid convulsions" according to a well-known technique. Experimental part. The Analgin and the test substances were administered intraperitoneally in the form of an aqueous suspension. Control group of rats was administered with isotonic sodium chloride solution. The studied compounds and isotonic sodium chloride solution were administered at a dose of 1/10 of LD50. Results. Among the compounds that were studied only some of them were close to the results of Analgin, other compounds showed lower activity. But among the 14 substances that were studied, some regularities have been noticed which can be applied for further purposeful synthesis of new molecules. Conclusions. For the first time, analgesic activity was studied for new 5-(furan-2-yl, 2-methylfuran-3-yl)-4-amino-1,2,4-triazole-3-thione. It was found that most compounds exhibit moderate activity. The pronounced analgesic effect, which approximated to the reference drug, is attributed to the sodium salt of 2-((5-furan-2-yl)-4-amino-1,2,4-triazole-3-ylthio)acetate and methylammonium 2-((5-furan-2-yl)-4-amino-1,2,4-triazole-3-ylthio)acetate. Some dependences of the substituents influence on the parameters of analgesic activity were established.